Does redistribution increase output? The centrality of labor supply - Kartik B. Athreya; Andrew Owens; Felipe Farah Schwartzman (Quantitative Economics, 2017)
The aftermath of the recent recession has seen calls to use transfers to poorer households as a means to enhance aggregate economic activity. The goal of this paper is to study the effects of wealth redistribution from rich to poor households on consumption and output in the short run. We first demonstrate analytically how the direction and size of the output effects of such interventions depend on labor supply decisions. We then show that in a standard incomplete-markets model extended to allow for nominal rigidities and parametrized to match the U.S. wealth distribution, wealth redistribution does lead to a temporary boom in consumption but a far smaller increase in output. Our results suggest substantial value in empirical research uncovering the distribution of marginal propensities to work in the population.
Keywords: D90; E21; E25; E63; 330; Multipliers; redistribution; labor supply; idiosyncratic risk